ANALISIS HUBUNGAN KADAR HEMOGLOBIN DENGAN PRESTASI BELAJAR MAHASISWA PENGHUNI ASRAMA POLTEKKES JAKARTA III - Husjain Djajaningrat; Chairlan Chairlan; Mardiana Mardiana (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Low hemoglobin (Hb) levelsaid as anemia,would reduce the ability to learn and endurance. Students who suffer from anemia will not have a high enthusiasm for learning because it is difficult to concentrate. Consequently, anemia indirectly affect the value of courses and learning achievement.Purpose to determine the relationship between Hb levels with the achievement of students studying at the health Polytechnic of Jakarta III. Methodsdesign of cross-sectional. Sample are 94 boarders health Polytechnic of Jakarta III, taken with proportional sampling technique. Instruments Hb levelsinvestigation byHbmethodeand questionaires. Data was analyzed with Chisquare. and Regression. Resultindicates that the average blood Hb level was 12.01 g% of students. Amounting to 40.4% female students had blood Hb levels <12 g% below normal and indicated there is anemia. Average achievement results 3.26 and <3.0 as much as 12.8%, Conclusions showed that level of Hb have significant related with learning achievement.There is a positive relationship between levels of Hb with learning achievement.